Globalization, Migration and Gender Equality: A Case from Okhaldhunga Village of Gorkha District - Ghimire, Harihar (Historical Journal, 2020)
Globalization is an intense of social relationship and closer integration of the countries and peoples of the world as well as it is a process involving increasing liquidity and growing multidirectional flows of people, objects, places and information. To become global is to be worldly and to be conscious of the current scenario of the present. The main objective of this paper is to analyze the effect of globalization on gender equality in rural society of Nepal. For the same, the study limits on the changing gender roles of 50 respondents have been analyzed in Okhaldhunga Village of Palungtar Municipality word no.4 of Gorkha District. Theory of globalization is applied and primary and secondary sources of information are used in this study. One of the result of this paper is women are enjoying modern technology and are increasing involvement in various local institutions and governance. Even though they are not aware about education and to be more advance life like men but they claim that they are more advanced than the previous generation women.